Euthanasia: Ethical Challenges of Shift from “Right to Die” to “Objective Decision” - Minocha, Vivek R.; Mishra, Arima (Annals of the National Academy of Medical Sciences (India), 2019)
Euthanasia is mercy killing to alleviate the pain and misery of moribund persons. The thought in this regard is “Right to Life” includes “Right to Die.” This paper examines the issue of euthanasia in advanced stage of terminal cases with no possibility of reversal and it has been argued that there is a case for lifting euthanasia from the domain of human rights “Right to Die,” bringing the issue as a matter for professional opinion, a kind of medical advice/prescription. Guidelines need to be framed and criteria are laid down and notified under which euthanasia can be recommended. The decision is taken whether or not the criteria laid down are fulfilled in an objective manner. Like for other medical interventions “informed consent” is essential. In consideration of safeguards the decision is entrusted to a medical board and is subject to a legal prescrutiny. Professionally prescribed decision will to a great extent reduce emotive response surrounding euthanasia. The family may not have to face a difficult dilemma in deciding about euthanasia. There may not be a necessity of “living will,” although it may still be useful. The change to treat euthanasia as a professional decision/medical advice will require making legal and administrative provisions to empower medical establishment to discharge responsibility of euthanasia. It is essential to legalize euthanasia with corresponding modifications of medical ethics and code of conduct prescribed by Medical Council of India, State Medical Councils, and other regulatory bodies. It is essential to identify the procedure for carrying out euthanasia and the personnel assigned to actually carry out. Injection of lethal substance in lethal dose may be a favored choice. Once final decision after legal prescrutiny is arrived for euthanasia, differentiating passive and active euthanasia is unnecessary. In one perspective, active euthanasia is less disturbing for the patient, family, and friends as withdrawal of supporting tubes leading to dehydration, wasting, and struggling for breath associated with passive euthanasia, which nullifies the basic tenet of euthanasia, can be avoided. There is a possibility of spill over benefit of “active euthanasia” in the form of opportunity to promote cadaveric organ transplantation. Caution has to be exercised for effective safeguards to prevent misuse. There is a case for consideration for brining decision-making process regarding euthanasia within medical professional assessment and implementation.
Keywords: euthanasia; active euthanasia; human rights; mercy killing; peaceful death; chronic vegetative state